2011
DOI: 10.1167/iovs.10-6079
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Vision Impairment for Children (IVI_C): Validation of a Vision-Specific Pediatric Quality-of-Life Questionnaire Using Rasch Analysis

Abstract: The modified IVI_C is a unidimensional, reliable, and valid scale for assessing QoL of children with vision impairment. It provides a valid means of assessing the outcomes of interventions and needs in children with vision impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
70
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 44 publications
2
70
0
1
Order By: Relevance
“…For example, the Impact of Vision Impairment for Children (IVI-C) instrument 13 can be used to assess the impact of visual impairment on VR-QoL, and the Cardiff Visual Ability Questionnaire for Children (CVAQC) 14 and the Functional vision questionnaire for children and young people with visual impairment 15 , to assess the impact on activities of daily living (functional visual ability).…”
mentioning
confidence: 99%
“…For example, the Impact of Vision Impairment for Children (IVI-C) instrument 13 can be used to assess the impact of visual impairment on VR-QoL, and the Cardiff Visual Ability Questionnaire for Children (CVAQC) 14 and the Functional vision questionnaire for children and young people with visual impairment 15 , to assess the impact on activities of daily living (functional visual ability).…”
mentioning
confidence: 99%
“…[56][57][58] Visual ability and QOL measures that assess the impact of vision loss in children have been examined in a variety of pediatric eye diseases, with most designed to evaluate children between 8 and 18 years of age. [59][60][61][62][63] Using the review process developed by the REiNS Patient-Reported Outcomes Subcommittee (see Wolters et al, this supplement), we reviewed the available pediatric questionnaires. Of these, 2 examined visual ability rather than visionspecific QOL.…”
mentioning
confidence: 99%
“…Although it only concerns children from 8 to 18 years old with different causes of impaired vision (albinism, congenital conditions, or juvenile-onset degenerative conditions) and it does not address treatment options, it does underline the major differences between families and professionnals about a patient's needs and concerns. 7,8 Wen et al 34 also showed that preschool children with strabismus had a significantly worse QOL than unaffected children, confirming what was long suspected.…”
Section: Ophthalmological Assessmentmentioning
confidence: 69%
“…Further, specialist instructors demonstrated greater concern for academic participation and instruction than for social skills. Cochrane and colleagues 8 further validated their questionnaire in 2011. Although it only concerns children from 8 to 18 years old with different causes of impaired vision (albinism, congenital conditions, or juvenile-onset degenerative conditions) and it does not address treatment options, it does underline the major differences between families and professionnals about a patient's needs and concerns.…”
Section: Ophthalmological Assessmentmentioning
confidence: 99%